1999
DOI: 10.1074/jbc.274.4.2255
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure Mapping of an RNA Ligand That Has High Affinity for the MetJ Repressor Protein and Interference Modification Analysis of the Protein-RNA Complex

Abstract: The secondary structure of an RNA aptamer, which has a high affinity for the Escherichia coli MetJ repressor protein, has been mapped using ribonucleases and with diethyl pyrocarbonate. The RNA ligand is composed of a stem-loop with a highly structured internal loop. Interference modification showed that the bases within the internal loop, and those directly adjacent to it, are important in the binding of the RNA ligand to MetJ. Most of the terminal stem-loop could be removed with little effect on the binding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is also possible that the HpNikR interaction is dictated in part by the structure of DNA, and it has been suggested that the palindromic sequence of the ureA promoter forms a hairpin structure [10]. In support of this hypothesis, in vitro selection of RNA apatamers revealed that the ribbon-helix-helix MetJ protein binds a consensus sequence with significant secondary structure [35].…”
Section: Discussionmentioning
confidence: 94%
“…It is also possible that the HpNikR interaction is dictated in part by the structure of DNA, and it has been suggested that the palindromic sequence of the ureA promoter forms a hairpin structure [10]. In support of this hypothesis, in vitro selection of RNA apatamers revealed that the ribbon-helix-helix MetJ protein binds a consensus sequence with significant secondary structure [35].…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the selected pool a number of negative control RNAs were also assayed. These were the naïve library used for the current selections, an individual aptamer from the same library but selected against the bacterial transcription factor MetJ (33) or an aptamer pool derived from an unrelated library and selected against the amyloid forming protein β2m (30). These controls allowed us to show that any effects were due to the selected region of the anti-RHD–CBFβ pool, and were independent of the fixed flanking regions.…”
Section: Resultsmentioning
confidence: 99%
“…Dephosphorylation of the in vitro transcribed RNA prior to end labeling was carried out according to standard procedures (31). The fluorescent-labeled 5Ј-hexachlorofluorescein (HEX) pseudoknot RNA was synthesized and high pressure liquid chromatography-purified as described previously (32). HEX phosphoramidite was obtained form Glen Research (Sterling, VA).…”
mentioning
confidence: 99%